CulturaGPT : Gamified Challenge-Based Learning Pathways with AI based Peer Tutoring - Chuah, Kee Man; Muhammad Kamarul Kabilan, Abdullah (2024)
CulturaGPT is an innovative project that replaces traditional lectures with an improvised challenge-based learning approach that embeds gamification over a 14-week semester. On the mythical island of Culturaeon, students work in teams with unique roles to solve real-world problems, guided by an AI-powered peer tutor customised with OpenAI’s GPT, which provides personalised feedback and assistance. Gamification elements motivate and reward students, making learning interactive and engaging. The impact is evident through increased engagement, higher achievement levels, and positive behavioural changes. End-of-course surveys revealed that students found the course design more engaging and beneficial for self-regulated learning. Observations indicated that even reluctant learners became more proactive and effective in their roles. Video reflections provided further insights into these changes. CulturaGPT demonstrates the effectiveness of challenge-based learning and offers a compelling model for the future of education.